Prevalence of malnutrition and associated factors of pond fish farmers from Noakhali Coast, Bangladesh - Pingki, F.H.; Hossain, M.B.; Nurul Amin, S.M.; Sultana, M.; Islam, M.M.; Arifur Rahman, A.F.M. (Triveni Enterprises, 2020)
Aim: Methodology: Results: Interpretation: Keywords: Current investigation was conducted to elucidate the occurrence of malnutrition and related factors of pond fish farmers from Noakhali coast, Bangladesh. Eighty male pond fish farmers, aged 18-70 years, from Noakhali Sadar, Subarnachar, Kobirhat and Ramgati upazila of Noakhali coast, Bangladesh were selected randomly for the investigation. Data were collected through questionnaire interview and survey, focus group discussion, cross check interviews, Body Mass Index, Mid Upper Arm Circumference and blood Hb level. Pearson correlation was used to determine the association between anthropometric and socio-demographic characteristics and simple linear regression were fitted to identify factors associated with malnutrition among pond fish farmers. The overall prevalence of malnutrition, overweight, obesity of pond fish farmers were 18.8%, 21.2% and 17.5%, respectively, based on BMI while the prevalence of malnutrition was 23.7% as per MUAC. The prevalence of mild anaemia (57.5%) was high compared to the global anaemia prevalence. 10% had no education while 22.5%, 20%, 7.5% and 5% had primary, secondary, higher secondary and bachelor education level, respectively. The highest (38.8%) annual income of the pond fish farmers was 1,300-1,785 USD. Significant variations (tested by one-way ANOVA) in nutritional status and socio-demographic characteristics were observed. Pearson correlations of age with MUAC exhibited significant (r = -0.271; p < 0.05) negative association, BMI was found positively and significantly correlated with annual income (r = 0.223; p< 0.05) and MUAC (r = 0.246; p< 0.05) Linear regression analysis revealed that the age of pond fish farmers had negative significant influence on MUAC and positive impact of annual income on BMI. The prevalence of malnutrition, mild anaemia with poor economic status were high among the pond fish farmers of Noakhali Coast. Therefore, community based health and nutritional education, effective public health and nutritional intervention programs, poverty alleviation program and economic growth may improve the overall health, nutritional knowledge and thus status of pond fish farmers.